Virtual laboratory for teaching control systems (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2013)
This article shows the process of creation and implementation of a virtual laboratory, which was developed as a class project by students of Mechatronics Engineering at the Autonoma del Caribe University, in order to support the knowledge acquired in the classroom and provide educational support to people interested in learning control systems. Students were trained in modeling dynamic and control systems using the Easy Java Simulation EJS software, which was designed for the creation of discrete computer simulations for training purposes. EJS allows dynamically display of several states of the components of a system, where each state is defined by a number of variables that change over time due to the iteration algorithm. The tendency of the virtualization of the course content makes indispensable the internet use as a key tool for learning outside the classroom, through the implementation of dynamic systems in EJS, it generates HTML files that allow us to post the created simulations in Java applets (applications within a Web page) on the website relating to the class. This project pursues to use, implement and build educational tools for visualization of phenomena described by a series of models governed by physical and electrical laws, supporting content learned in class while the student can be part of it expanding the database with their proposals.
Keywords: virtual; laboratory; teaching; engineering; control